The Effect of Toxic Leadership on Turnover Intention, Counterproductive Work Behaviour, and Job Satisfaction - Harroviantin, Francisca; Tandelilin, Elsye (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to analyze the influence of toxic leadership on turnover intention, counterproductive work behavior (CWB), and job satisfaction in employees of PT. X Indonesia. The phenomenon of increasing employee resignation rates and indications of negative work behavior is an important background for this study. This study used a quantitative approach with a census method, involving 54 respondents from various levels of position. The data analysis technique was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0 software. The results of the external model evaluation showed that all indicators used met the criteria for validity and reliability, with the value of loading factor, Average Variance Extracted (AVE), and composite reliability above the minimum threshold. Furthermore, the results of the inner model test showed that toxic leadership had a significant positive effect on turnover intention (? = 0.729), and CWB (? = 0.697), and had a significant negative effect on job satisfaction (? = -0.683), all with a p value of < 0.001. The R² value obtained indicates the model's predictive ability to be moderate for all endogenous variables. This study confirms that toxic leadership is a determinant factor that significantly decreases job satisfaction and increases employee exit intention and counterproductive behavior. The implications of this study emphasize the importance of early detection of toxic leadership practices and the development of a healthy organizational culture through managerial interventions and strategic HR policies.